IL-32 as a potential biomarker and therapeutic target in skin inflammation - Wallimann, Alexandra; Schenk, Mirjam (Frontiers in Immunology, 2023)
IL-32 is a recently described cytokine that performs a variety of functions under inflammatory conditions. Serum IL-32 has been shown to be elevated in several diseases, including type 2 diabetes, cancer, systemic lupus erythematosus, HIV infection, and atopic diseases including atopic dermatitis. There are nine different isoforms of IL-32, with IL-32ℽ being the most biologically active one. The following review summarizes the different roles of the various IL-32 isoforms in the context of skin inflammation, with a focus on atopic dermatitis.